Pengaruh Sistem Informasi Akuntansi dan Promosi terhadap Volume Penjualan dengan Kualitias Produk Sebagai Variabel Intervening di PT. Saudara Karya - Arifin, Zaenal; Agus, Agus; Hartadi, Arif; Aziz, M.; Riyadi, Slamet; Pandin, Maria Yovita R (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Accounting information systems can aid businesses in enhancing sales volume and profitability, notwithstanding the challenge of increasing sales. This research investigates how promotions and management accounting information systems influence product quality, and explores whether product quality serves as a significant mediator. A survey was conducted among customers of PT. Saudara Karya Surabaya, involving 102 respondents selected through purposive sampling of customers who had completed at least one transaction. Structural equation modelling was employed to analyze the collected data. The findings indicate that both management accounting information systems and promotional strategies positively impact product quality. Furthermore, the study reveals that the relationship between promotions, management accounting information systems, and sales volume is mediated by product quality. This study contributes to the theoretical framework of marketing strategy by integrating concepts of product.